2019
DOI: 10.5758/vsi.2019.35.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Arterial Mediolysis: A Case Study and Review of the Literature in Accurate Diagnosis and Management

Abstract: Segmental arterial mediolysis (SAM) is a rare noninflammatory, nonarteriosclerotic arteriopathy of an unknown etiology. It most commonly affects the medium-sized vessels of the abdomen and is characterized by the disruption of the arterial medial layer. Although histological confirmation remains the gold standard in diagnosis, the use of computed tomography angiography (CTA) has greatly aided the diagnosis and surveillance of SAM. Given its rarity and angiographic similarities to other vasculopathies, the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…9 Differential diagnosis of this disease is very important, as there are multiple mimics that could make diagnosing SAM particularly challenging. 2,5,7,9,13 Atherosclerosis as a cause needs to be considered, but patients usually have diffuse atherosclerosis of multiple vessels, and the disease affects artery bifurcations. 5 SAM is usually isolated in medium sized vessels and has no preference for bifurcations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Differential diagnosis of this disease is very important, as there are multiple mimics that could make diagnosing SAM particularly challenging. 2,5,7,9,13 Atherosclerosis as a cause needs to be considered, but patients usually have diffuse atherosclerosis of multiple vessels, and the disease affects artery bifurcations. 5 SAM is usually isolated in medium sized vessels and has no preference for bifurcations.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10][11] However, the disease has been reported in all age groups, including neonates. 3,5 No comorbidities have been associated with SAM 3 , but most studies, reported hypertension in a significant number of patients with the disease. 2,3 However, it is possible that this finding reflects the incidence of hypertension in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of angiographic diagnosis is stenosis, occlusion, aneurysmal formation, arterial dilatation, and dissection of medium-sized vessels. Numerous lesions are often identified, affecting arteries in a segmental skip pattern, with the diseased segments demonstrating the involvement of the circumference or only a portion of the arterial wall (5). Arterial dissections account for most of the reported cases of SAM, followed by pseudoaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nonspecific clinical presentation, SAM can mimic different pathologies and conditions, including atherosclerosis alterations, systemic inflammatory vasculitis such as granulomatosis with polyangiitis, polyarteritis nodosa, eosinophilic granulomatosis with polyangiitis, Kawasaki disease or Takayasu’s arteritis, mycotic aneurysm, cystic medial necrosis (in patients with Marfan Syndrome), fibromuscular dysplasia, and infectious processes. Epidemiological, laboratory, histology, and radiological findings need to be carefully analyzed and integrated to obtain the correct diagnosis and to guide the treatment [ 21 , 22 ]. The natural history of SAM is unpredictable and requires continued surveillance over several years.…”
Section: Discussionmentioning
confidence: 99%